(untitled) (Quinto Sol, 2026)
The objective of this article is to reconstruct the foundations, purposes, composition, trajectory, publications, and declarations of Afirmación Argentina (Argentine Affirmation), in order to specify its place within the nationalist spectrum of the time and its position on the local political scene. This nationalist political group emerged in 1940 as part of the proliferation of groups and publications of this ideological orientation, motivated by the outbreak of war, the increase in military conspiracies of this kind, and the search for a broader social base of support. Its activities continued until after the 1943 coup d’état and included figures from diverse backgrounds. In addition to leaders of conservative and nationalist origin, prominent figures from the cultural sphere joined, such as Homero M. Guglielmini, Lisardo Zía, Carlos Astrada, and Armando Cascella. One of its fundamental objectives was the defense of Argentine neutrality during World War II; this stance brought it closer to other nationalist groups. However, what characterized Afirmación Argentina was its link with the conservative government of Ramón S. Castillo (1940-1943).